Answer:
The sum of the two integers is 23
Explanation:
Let one integer be x and the other integer be y
Then according to the statement "One positive integer is 3 greater than 4 times another positive integer.."
x be the integer that is One positive integer is 3 greater than 4 times another positive integer.
Then
x= 3+4y----------------------------------(1)
Product of the two integer is 76, this can written as
![x * y =76](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k07o2hgel7flpt5e4fvmbbkk0xfkp8iz66.png)
substituting the values of x from eq(1)
![( 3+4y) * y =76](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ewja70c5hrd9tre9cjvpq3x8j7kjccp6mr.png)
![3y + 4y^2 = 76](https://img.qammunity.org/2020/formulas/mathematics/middle-school/j82yepivvzpz92cfzm7uhal7pni2nlei62.png)
![3y + 4y^2-76= 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1xlna9hr6fcz9hhj35wgwhvlb1ltesedzn.png)
![4y^2 + 3y -76= 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/j091wiv5p5f06oeauic10qevb8dlaljvid.png)
Solving the quadratic equation equation we get
![x=(-b \pm √(b^2-4ac))/(2a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hgars81yntwdhytaoyvvvlu2ao3yrckt4d.png)
here
a = 4
b= 3
c = -76
susbtituting the above values in the formula
![y=(-3 \pm √(3^2-4(4)(-76)))/(2(4))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d6qhxl1ardibo48lsckpbzgwrwd69w3u5c.png)
![y=(-3 \pm √(9- 4(4)(-76)))/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/yfp9mn17gngt0tkum389fe4j4a3hor43p2.png)
![y=(-3 \pm √(9- (16)(-76)))/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jp5y2s4pjtvlvmr3502fl5d25zvaalame8.png)
![y=(-3 \pm √(9- (-1216)))/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bqc8li6gs08ccgvkfz1vzs7rix6ieyfx5x.png)
![y=(-3 \pm √(9 + 1216))/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/g0xc8nd2gyxngjtf3pm2rry5jn4l25ivsk.png)
![y=(-3 \pm √(1225))/(8)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uhaslzzngr5qfjfcoh4c95t4pnrzl8rg1h.png)
y= 4 y = −4.75
Since in the question it is given that it is a positive integer
so y = 4
substituting y=4 in eq (1) we get,
x= 3+4(4)
x= 3+16
x= 19
The sum of the two integers
=> x + y
=> 19+4
=>23